Optimization of Technological Parameters of Power Efficient Roller Mill - P. E. Vaitekhovich; V. S. Frantskevich (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
Milling process in the closed cycle of a roller mill has been analyzed and its diagram has been drawn up. The diagram objectively shows influence of all factors on milling process. Optimization technique of the main technological mill parameters is proposed in the paper. Results on optimization are confirmed experimentally. The optimization technique and its approbation have shown that it is possible to calculate with high accuracy maximum milling rate and productivity of a roller mill at optimum values of main parameters.